Get out in front!: an evaluation of a media workshop for young elite sportswomen - Evers, Clifton; le Masurier, Megan (University of Nottingham, Deakin University & University of New South Wales, 2011)
Research into sport and gender in Australia has suggested that teenage girls are still under-represented in sport and physical activity when compared to boys of similar age groups. Sports such as football and cricket dominate media coverage (and sponsorship interest) and remain male-dominated. While there has been increasing opportunity for young girls to participate in mixed and non-traditional sports, the perception of these sports as predominantly a masculine pursuit at pre-elite and elite levels affects assumptions about adolescent girls’ competency and interest in sporting participation. This article is about how young elite sportswomen view the fact that women’s sports continue to struggle for recognition and coverage in newspapers, magazines, radio and television stations. This type of representation impacts on women’s sports credibility.